PENGARUH PENGAWASAN KERJA DAN KEDISIPLINAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA - Septriani, Rona Nimas; Hardiningrum, Iing Sri; Mahaputra, Agung Pambudi; Azizah, Siti (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The problem raised in this study is the lack of optimal work supervision and discipline of the state civil apparatus. The purpose of this study was to determine the partial and simultaneous effect of supervision and discipline on the performance of ASN in the District Office of Responsibilitygunung, Tulungagung Regency. The study used a quantitative approach, with a population of 51 people consisting of 45 ASN and 6 Non ASN. The sample was selected as many as 45 respondents with purposive sampling method. Collecting data using a questionnaire instrument and data analysis techniques used are descriptive and inferential statistics through validity, reliability, classical assumption test, multiple linear regression test and research hypothesis testing. Based on the results of the study, the findings of the regression equation Y = 24,532 + 0,552 X1 + 0,203 X2. Based on the partial test it was found that the value was significant. t (0.004) <0.05 means that partially there is a positive and significant influence between work supervision on employee performance. Significant value. t (0.002) <0.05, which means that partially there is a positive and significant influence between Discipline on the Performance of the Officers of the District Office of Tanggunggunung Tulungagung. Simultaneously supervision and work discipline have an effect on employee performance as evidenced by the value of Fcount 23,024 > Ftable = 2,810 and the value of Sig. F of 0.010 < 0.05.